Lipidomic Perturbations in Cynomolgus Monkeys are Regulated by Thyroid Stimulating Hormone - Xu, Tao; Yang, Yanling; Huang, Xing; Ren, Jianhong; Xu, Ting; Xie, Wei (Frontiers in Molecular Biosciences, 2021)
Thyroid disease affects an estimated 200 million people worldwide, and is commonly associated with increased blood lipid levels. However, the mechanism by which thyroid-stimulating hormone (TSH) affects lipid profiles is not clear. Twenty-four cynomolgus monkeys were treated with a novel exogenous recombinant human TSH (rhTSH) (SNA001) at 9 ug kg-1, 22 ug kg-1, or 54 ug kg-1, and reference rhTSH (Thyrogen®) at 22 ug kg-1. The primary TSH (SNA001) pharmacokinetic (PK parameters increased in a dose-dependent manner across the dose range of 9 ug kg-1, 22 ug kg-1, or 54 ug kg-1. Peak triiodothyronine (T3) and thyroxine (T4) levels were reached within 24 h after rhTSH administration, which was delayed by approximately 20 h. In total, 420 lipid species were detected and quantified by ultra-performance liquid chromatography high resolution spectrometry (UPLC-HR-MS)-based lipidomics. Notably, peak levels of lipid accumulation, particularly sphingomyelin (SM) and triglycerides (TG), appeared at 4 and 24 h, which was consistent with the pattern of TSH and T3/T4 levels, respectively. According to weighted correlation network analysis (WGCNA), perturbations of many lipid species were strongly correlated with TSH and T3/T4 levels. TSH and the stimulated T3/T4 levels and lipid profiles following SNA001 administration were comparable to those after administration of the reference rhTSH (Thyrogen®). The plasma lipidome and changes in lipid levels after rhTSH stimulation were associated with TSH and T3/T4 concentrations. T3/T4 and lipid profiles were delayed after TSH stimulation. Such phenomena require further exploration.